Matrix interference from Fc–Fc interactions in immunoassays for detecting human IgG4 therapeutics. (October 2015) - Partridge, Michael A; Karayusuf, Elif Kabuloglu; Dhulipala, Gangadhar; Dreyer, Robert; Daly, Thomas; Sumner, Giane; Pyles, Erica; Torri, Albert
Background: An assay measuring an IgG4 biotherapeutic in human serum used a drug-specific monoclonal antibody (mAb) capture reagent and an antihuman IgG4 mAb as detection reagent. However, serum IgG4 binding to the capture mAb via Fc-interactions was detected by the anti-IgG4 mAb, causing high background.Results: Two approaches were developed to minimize background; incorporating a mild acid sample preparation step or using the Fab of the capture antibody. Either strategy improved signal:noise dramatically, increasing assay sensitivity >20-fold. Biophysical analyses of antibody domains indicated that noncovalent Fc oligomers could inhibit the background.Conclusion: Matrix interference from human IgG4 binding to the capture mAb was reduced with a Fab fragment of the drug-specific capture antibody or by incorporating a mild acid sample treatment into the assay.